ACLIMATAÇÃO DE MUDAS DE BANANEIRA (MUSA SPP.) ’PRATA’ (AAB) EM DIFERENTES SUBSTRATOS - SILVA, GILSON DOURADO; FERNANDES, ADRIANO ALVES; PEREIRA, MARLON CRISTIANO TOLEDO; BRUCKNER, CLAUDIO HORST; SIQUEIRA, DALMO LOPES DE (Revista Ceres, 2015)
.